2015
DOI: 10.1039/c4ra10254a
|View full text |Cite
|
Sign up to set email alerts
|

New cellulose–silica composite IMAC/C18 for the selective enrichment of phosphorylated molecules and the improved recovery of hydrophilic species

Abstract: Cellulose and silica are the traditional quality sorbents with range of reported applications, particularly for the hydrophilic biomolecules. Considering those characteristics, cellulose and silica are brought into a composite form to take the benefits on a single platform. Choice of cellulose and silica is made to obtain complete hydrophilic composite, followed by its derivatization for the selective enrichment of phosphopeptides and as desalting material prior to the mass spectrometric analysis. The composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Cellulose–SiO 2 –IMAC–Sm 3+ (Najam‐ul‐Haq, Jabeen, Shafiq, Sajid, & Saba, ), SiO 2 –La 2 O 3 composite (Jabeen et al, ) and Fe 3 O 4 @Sm 2 O 3 core–shell nanocomposites (Jabeen et al, ) were synthesized using the reported protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Cellulose–SiO 2 –IMAC–Sm 3+ (Najam‐ul‐Haq, Jabeen, Shafiq, Sajid, & Saba, ), SiO 2 –La 2 O 3 composite (Jabeen et al, ) and Fe 3 O 4 @Sm 2 O 3 core–shell nanocomposites (Jabeen et al, ) were synthesized using the reported protocols.…”
Section: Methodsmentioning
confidence: 99%
“…The tips were washed with 80% ACN in 0.2% TFA followed by DHB buffer (110 mg of DHB in 0.5% ACN) and deionized water. The elution was performed using 1.5% aqueous ammonium hydroxide solution for phosphopeptides and 1% ammonium hydroxide in chloroform for phospholipids . The eluted fractions were subjected to MALDI-MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The elution was performed using 1.5% aqueous ammonium hydroxide solution for phosphopeptides and 1% ammonium hydroxide in chloroform for phospholipids. 12 The eluted fractions were subjected to MALDI-MS analysis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new cellulose–silica composite IMAC/C18 sorbent that was derivatized for the selective enrichment of phosphopeptides has been reported . The IMAC/C18 sorbent was utilized to enrich phosphopeptides from a complex sample in which β‐casein is spiked in dephosphorylated HeLa cell extract.…”
Section: Methodologies Used To Reduce the Complexity Of Proteomic Sammentioning
confidence: 99%